Phosphorylation of Dynamin-Related Protein 1 (DRP1) Regulates Mitochondrial Dynamics and Skeletal Muscle Wasting in Cancer Cachexia - Mao, Xiangyu; Gu, Yihua; Sui, Xiangyu; Shen, Lei; Han, Jun; Wang, Haiyu; Xi, Qiulei; Zhuang, Qiulin; Meng, Qingyang; Wu, Guohao (Frontiers in Cell and Developmental Biology, 2021)
Background: The underlying mechanisms of skeletal muscle atrophy under cancer-associated cachexia (CAC) are still unknown. Disrupting mitochondrial dynamics of myocyte may contribute to this process, of which, Dynamin-Related Protein 1(DRP1), is a pivotal protein kinase. Here we investigated the involvement of DRP1, mitochondrial fission and myotubes atrophy of cancer cachexia. Methods: The clinical characteristics associated with muscle atrophy, and the morphological changes of myotubes and mitochondrial were investigated. DRP1 expression was explored at the transcript and protein level, as well as phosphorylation level. To further study the mitochondrial fission regulated by DRP1, cells model of cancer cachexia was built. The morphology of myotubes was observed by myosin stain, mitochondrial dynamic was detected by mito-tracker stain after down-regulated or strengthened the expression of DRP1 or inhibited DRP1 with different concentration of Mdivi-1. Moreover, we explored the mitochondrial function, by detecting the expression of COX IV, Cyto C and mtUPR. Results: Related clinical indicators of skeletal muscle wasting in patients with CAC were significant lower compared with controls (P < 0.05). The myocyte cross sectional area in CAC was also shortened than controls (5825.53 Vs. 2929.64um2, P < 0.05). Furthermore, severe mitochondrial swelling was observed in CAC (2.15 folds, P < 0.05). The mRNA and protein level of DRP1 in CAC was mild higher than controls (1.48 folds, P < 0.05), however, the phosphorylation level of DRP1(ser616) was obvious higher in CAC (1.68 folds, P < 0.05). In vitro, under C26 CM, the diameter of myotube was shortened and mitochondria was in a more fission-state, which could be obviously rescued by Mdivi-1 (5uM and 10uM). Moreover, as the expression of DRP1 increased, the level of COX IV and Cyto C decreased significantly, while mtUPR increased obviously (P < 0.05), all of which could be reversed by knocked down and changed the phosphorylation pattern of DRP1. Conclusions: Phosphorylated DRP1 is responsible for skeletal muscle atrophy and mitochondrial fission in cancer cachexia. Blocking DRP1 could promote mitochondrial fusion, improve the function and alleviate the muscular atrophy.